If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 89 = 10x + 8 Reorder the terms: 89 + x = 10x + 8 Reorder the terms: 89 + x = 8 + 10x Solving 89 + x = 8 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 89 + x + -10x = 8 + 10x + -10x Combine like terms: x + -10x = -9x 89 + -9x = 8 + 10x + -10x Combine like terms: 10x + -10x = 0 89 + -9x = 8 + 0 89 + -9x = 8 Add '-89' to each side of the equation. 89 + -89 + -9x = 8 + -89 Combine like terms: 89 + -89 = 0 0 + -9x = 8 + -89 -9x = 8 + -89 Combine like terms: 8 + -89 = -81 -9x = -81 Divide each side by '-9'. x = 9 Simplifying x = 9
| 163-7x=29x+15 | | (x^3)/18 | | 9x+3=187 | | x^2+6x+8=24 | | (n+3)*6=72 | | S=C+x | | a/4+4=8 | | x^2-14x+4=0 | | 6x-12y-24=0 | | 14+14z=-8-6z | | Y=-.75x+4.5 | | 5(3-7a)=-230 | | 4x+9=99-6 | | Y=-.75x+18 | | 9a-4=68 | | 9x+16=9x+20 | | y=-15x^3+3x | | x^2-11x=8 | | x+2x=93 | | -3k-8=-2 | | 6n+5=-85-9n | | 2x^2-15-20=0 | | 3x+9=9x+99 | | 4(y-1)=y+13 | | 420/36=f/30 | | 4y+1=y+13 | | -56-3v=7-10v | | 2x-10=2x+10+1 | | 4x-113=4x+9 | | 3c+5c-5c= | | 3x+28=9x-8 | | 11(p-3)=2y+2 |